2021
DOI: 10.7759/cureus.18461
|View full text |Cite
|
Sign up to set email alerts
|

Tibialis Posterior Transfer for Foot Drop: The Difference in Outcome for Two Different Attachment Sites

Abstract: IntroductionCommon peroneal nerve injury leading to foot drop is of multifactorial etiology. The goal is to restore a normal toe-heel gait. Various static or dynamic surgical options are being performed. Among all, tendon transfer is the most commonly performed procedure with its different dorsal attachment sites on the foot i.e. tendon to bone or tendon to tendon transfer. The objective of our study was to evaluate the outcomes of two methods of transfer in terms of attachments sites on functional outcomes. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The patients were divided into two groups according to the type of surgical technique for fixing the posterior tibial tendon to the dorsum of the foot (tibial posterior to the 2nd metatarsal, n=17), in group 1, and group 2 (n=15), in the posterior tibial tendon for transferring the anterior tibial tendon. 15 No significant postoperative complications were observed in either group, only one patient had a surgical site infection adequately treated with antibacterial prophylaxis. The results of the surgeries, six months after the operation, confirmed that the majority of patients in both groups were classified as excellent to good, according to the scale described by Carayon et al And the researchers were able to confirm statistically that, in this sample, the insertion in the second metatarsal presents more favorable results in relation to the insertion in the tibialis anterior.…”
Section: Study Technique Conclusionmentioning
confidence: 81%
See 4 more Smart Citations
“…The patients were divided into two groups according to the type of surgical technique for fixing the posterior tibial tendon to the dorsum of the foot (tibial posterior to the 2nd metatarsal, n=17), in group 1, and group 2 (n=15), in the posterior tibial tendon for transferring the anterior tibial tendon. 15 No significant postoperative complications were observed in either group, only one patient had a surgical site infection adequately treated with antibacterial prophylaxis. The results of the surgeries, six months after the operation, confirmed that the majority of patients in both groups were classified as excellent to good, according to the scale described by Carayon et al And the researchers were able to confirm statistically that, in this sample, the insertion in the second metatarsal presents more favorable results in relation to the insertion in the tibialis anterior.…”
Section: Study Technique Conclusionmentioning
confidence: 81%
“…The results showed little or almost no intercurrence unfavorable to the patients and the researchers reported that ten patients returned to daily activities and four returned to the practice of physical activity without using the orthosis. 14 In the study carried out by Khan et al, 15 the researchers also stated, as seen in Wen et al, 11 regarding the existence of controversies regarding the transfer procedure (circumtibial versus interosseous) and location of fixation on the dorsum of the foot (tendon-bone or tendon-tendon), but it agrees with the favorable authors, seen in this review, on the choice of the dynamic tendon transfer technique being considered the gold standard for restoring foot dorsiflexion and allowing almost normal functional activity, in addition to preventing equinovarus deformity caused by the posterior tibial tendon. Their research was based on the technique described by Carayon et al, and on a modification of the classic Barr procedure, when they used two different fixation sites on the foot, one with tendon-bone fixation, that is, rolling the posterior tibial tendon around the second metatarsal and, the second, to the anterior tibial tendon.…”
Section: Study Technique Conclusionmentioning
confidence: 98%
See 3 more Smart Citations